Analisis Pengaruh Pengeluaran Pemerintah Sektor Pendidikan dan Kesehatan Terhadap Pertumbuhan Ekonomi dan IPM di Langsa - Muammar Kaadafi Z; Asnidar; Miswar (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2023)
This research aims to analyze the influence of government expenditures in the education and health sectors, as well as economic growth, on the Human Development Index in Langsa City. The independent variables used in this study are government expenditures in the education and health sectors, while the dependent variables are economic growth and the Human Development Index. The data used in this research are secondary data from the period of 2010-2021 in Langsa City, collected through annual time series data collection with a quantitative nature. The research findings indicate that government expenditures in the education sector have a positive influence on economic growth and the Human Development Index. Government expenditures in the health sector have a positive influence on economic growth but a negative influence on the Human Development Index. Additionally, economic growth has a positive influence on the Human Development Index.